Resection of primary gastroenteropancreatic neuroendocrine tumors in the presence of irresectable liver metastases. (November 2016) - Wadsworth, Philippa K; Jones, Robert P; Poston, Graeme J
Gastroenteropancreatic neuroendocrine tumors often present at an advanced stage and carry a variable prognosis, with many patients living long periods even with metastatic disease. Resection of the primary tumor when liver metastases are unresectable is a contentious subject with no consensus between existing guidelines. A number of recent studies have suggested a potential survival benefit as well as improved symptom control with resection. With variable results from nonoperative management strategies, the risk:benefit ratio of resection of the primary tumor may be favorable for carefully selected patients.